Ten steps to ITSM success : a practitioner's guide to enterprise IT transformation - Esposito, Angelo (IT Governance Publishing, 2013)
Ten Steps to ITSM Success helps IT to prepare for this role by providing a detailed and practical guide to implementing ITSM best practices. It is aimed at ITSM practitioners and consultants, but will also be of interest to IT Directors and C-suite executives looking to transform the role of IT into a value-creating business partner, to establish a service management culture, and to drive improvements in their respective organizations.